Problematika Hukum atas Kelembagaan dan Operasional Bank syariah - Nurul Iman (Qisth : Jurnal Studi dan Penelitian Hukum Islam, 2025)
Islamic banking emerges as an alternative financial system based on Islamic Sharia principles, such as the prohibition of usury (riba), uncertainty (gharar), and gambling (maysir), while upholding justice and partnership. However, in practice, the institutional framework and operational implementation of Islamic banks face various legal issues, both normatively and practically. This study aims to explore the legal problems surrounding the institutional structure and operational practices of Islamic banks in Indonesia. Using a qualitative library research method and a normative legal approach, the study finds several challenges, including regulatory dualism, disharmony between DSN-MUI fatwas and regulations by the Financial Services Authority (OJK) or Bank Indonesia (BI), and inconsistencies in the application of Sharia contracts in banking operations. These problems may undermine the credibility of Islamic banks and create public skepticism regarding their Sharia compliance. Therefore, legal harmonization and institutional governance reform are essential to ensure that Islamic banks operate in full accordance with Sharia values.